Finite element failure analysis of wires for civil engineering applications with various crack-like laminations - Adewole, Kazeem Kayode (2015)
This paper presents the finite element (FE) failure predictions and analyses of a typical wire for civil engineering applications with various crack-like lamination types (Single and double), geometries (straight-end and inclined-end) and orientations (longitudinal, lateral and transverse). FE prediction and analysis of the failure of notched pre-cracked wires with a surface across-the-thickness crack-like lamination validated with experimental results are also presented. The FE predicted fracture shape for the notched pre-cracked wires that consists of a cup and cone fracture shape below the bottom tip of the surface across-the-thickness crack-like lamination agrees with the experimental fracture shape. Wires with the double straight-end and double inclined-end crack-like/line-type laminations exhibit a “slant-middle W” and a “zigzag” fractures respectively. Above and below the lateral mid-width across-the-thickness lamination, the wires with the lateral mid-width across-the-thickness lamination exhibit a combination of a transverse mid-thickness flat fracture that is perpendicular to the lateral mid-width across-the-thickness lamination and negatively inclined slant fractures on each side of the mid-thickness flat fracture at the remaining outer edges of the wire's thickness. On both the front and back sides of the transverse mid-thickness across-the-width lamination, the wires with the transverse mid-thickness across-the-width lamination exhibit a combination of transverse flat fractures parallel to the transverse mid-thickness across-the-width lamination and positively inclined slant fractures at the outer edges of the wire's thickness. FE failure analysis reveals that fracture initiations do not always begin at the termini of every longitudinal crack-like/line-type lamination as reported in a published fractographic failure analysis report of wires with longitudinal crack-like laminations. Fracture initiation only begins at the termini/tip of longitudinal inclined-end crack-like laminations and at the termini/tip of transverse and lateral laminations. FE failure analysis also reveals that wires with single straight-end, double straight-end and double inclined-end longitudinal crack-like/line-type laminations do not exhibit cup and cone fractures as reported. This work further demonstrates the need to employ FE failure analysis as a complimentary or alternative failure analysis approach where the destruction/alteration of the fracture markings by corrosion could affect the accuracy of fractographic failure analysis.